An Approach to Establishing Diagnostic Reference Levels in Interventional Pediatric Cardiology from Different Regions of Brazil - Viviane K. Asfora; Marcelo B. Freitas; Regina B. Medeiros; Hugo R. Schelin; Akemi Yagui; Marcus V. L. Oliveira; Luiz M. S. A. Leite; Guillermo A. Lopez; Maryanna R. S. Roberto; Fabio L. Gagetti; Pablo H. O. Souza; Bruna Vargas; et al. (MDPI AG, 2024)
Diagnostic reference levels (DRLs) are a pivotal strategy to be implemented since pediatric interventional cardiology procedures are increasing. This work aimed to propose an initial set of Brazilian DRLs for pediatric interventional diagnostic and therapeutic (D&T) procedures. A retrospective study was carried out in four Brazilian states, distributed across the three regions of the country. Data were collected from pediatric patients undergoing cardiac interventional procedures (CIPs), including their age and anthropometric characteristics, and at least four parameters (number of images, exposure time, air kerma-area product-PKA, and cumulative air kerma). Data from 279 patients undergoing CIPs were gathered (147 diagnostic and 132 therapeutic procedures). There were no significant differences in exposure time and the number of images between the D&T procedures. A wide range of PKA was observed when the therapeutic procedures were compared to diagnostics for all age groups. There were significant differences between the D&T procedures, whether grouping data by patient weight or age. In terms of cumulative air kerma, it was noted that no value exceeded the level to trigger a monitoring process for patients. This study shows that it is possible to adopt them as the first proposal to establish national DRLs considering pediatric patient groups.